Hydraulic characterization of PVC-O pipes by means of transient tests - Ghazali, M. F.; Nizwan, Che Ku Eddy; Ismail, Nurazima; Sani, M. S.M.; Yusof, Mohd Fadhlan M.; Mohamed, Zamri (2019)
This report is proposing and experimenting on the newly found mathematical algorithm for analyzing and processing a nonlinear and non-stationary signal for decomposing and imposing the signal into multiple decomposition of the signal. The objective of this thesis is to construct and develop the experiment procedures for the leakage detection in medium density polyethylene (MDPE) pipeline. The thesis explains upon on how the process that are being introduced and being applied in the method of Ensemble Empirical Decomposition Method (EEMD) with signal masking, with it then the method would analyze the position of the leakage of the pipeline. The pipe that is being used to fabricate the experiment setup is the PN-16 pipe with a diameter of 63mm, and the length of the total pipeline is 118m. The system that is being used in the experiment and will be explained in the thesis is the method of water hammering in which the water would be abruptly shut off and that would induce an impulse throughout the pipeline, with that in turn would cause the system into a surge of water wave. The data analysis of the signal that then to be decomposed into a series of wave composition with the use of EEMD signal masking method by using the matrix laboratory (MATLAB) software. The series of decomposition of signals is then carefully selected on where the supposed reflected intrinsic mode function (IMF). These IMFs that where being displayed by using a mathematical algorithm, that is known as Hilbert Transform (HT) spectrum. With this, the IMF signal was analyzed, and the difference of the time would be obtained and calculated. Finally, the analyzed data could be compared with the actual measurement of the leakage in term of percentage of errors. The obtained results indicate that when the distance of the leakage increase, the accuracy of the detected data would be less accurate, and when the pressure of the pipeline decreases, the detected data would be less accurate also. The detected data was being influenced by various different types of noises that in turn would also compromise the result that would be obtained. In order to improve the data of the signal, it was proposed that we reduce the features on the pipe as this would also be detected by the transducer, extend the length of the pipe from the pump so that the noise from the water pump would be reduced, and lastly improve the MATLAB coding so that the sampling rate of the signal is optimized with the process so that the analysis for the IMFs would have less mode mixing problems.